(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Withthe emergence of data warehousing, Decision Support Systems have evolved to itsbest. At the core of these warehousing systems lies a good database managementsystem. Database server, used for data warehousing, is responsible to providerobust data management, scalability, high performance query processing andintegration with other servers. Oracle being the initiator in warehousingservers, provides a wide range of features for facilitating data warehousing. Thispaper is designed to review the features of data warehousing - conceptualizingthe concept of data warehousing and lastly, features of Grade servers forimplementing a data warehouse.